Resolving Solubility Problems and Providing an Overview of Excipients to Boost Oral Drug Bioavailability (Asian Journal of Pharmaceutics (AJP), 2023)
In this study, the methods and resources to improve the bioavailability and solubility of poorly soluble medicationsare covered. Common supports that may function as solubilizers, disintegrants, and binders in tablet formulationsinclude hydroxypropyl cellulose (HPC) and starch. It has been shown that HPC increases the solubility and rateof drug dissolution for medications such as caffeine and itraconazole. HPC is soluble in water and polar organicsolvents. When combined with other components, it may be used as a binder, solvent, or partly preformed cornstarch to assist in making poorly soluble medications more soluble and bioavailable. In most countries, the use ofStarch 1500 and microcrystalline cellulose has led to commercial success in new automotive generic and over-thecountermarket categories. Decreased reliability offer moisture action, which is crucial for coatings and packingfilms. The study states that these procedures and the use of excipients may be useful means of resolving solubilityissues and enhancing oral medication bioavailability.